Psychological dynamics of inheritance distribution in Islam: from principles and practices to future research directions - Sulong, Jasni; Mohd Mahudin, Nor Diana (IIUM Press, 2021)
In Islam, wealth is owned by Allah (SWT), and it is merely lent to humans to cater to their ephemeral needs. Therefore, under Islamic law, any property in the inheritance should be transferred immediately to the rightful heirs after the demise of the owner. The heirs will then replace the original owner in possessing the properties according to the proportions prescribed by Islamic law. This process of handling the inheritance should be within the purview of the inheritance laws (i.e., al-farāʼiḍ) according to the Sharīʻah. The implementation of this process, however, can be challenging and may not necessarily be smooth sailing for all involved. Hence, to ensure that a smooth-flowing process of inheritance distribution is maintained, all heirs or beneficiaries must be cooperative and willing to expedite the process.